Thermal comfort of urban spaces in hot humid climate - Abdul Majid, Noor Hanita (2004)
The environmental conditions of urban spaces in relation to comfort have been the prevailing issues in discussion of climate change and urban environment. However, there are very few researches conducted in relation to urban spaces in hot humid tropical climate. This topic has been studied by Noor Hanita (2000), where investigations were done to evaluate the micro climate conditions of plaza adjacent to tall buildings (PATB). This paper describes the experiments done at several sites in Kuala Lumpur that presents results in form of modified Predicted Mean Vote (PMVm) developed by the author. The predicted votes are based on Fanger’s PMV index that is correlated to Thermal Sensation Votes (TSV) from outdoor field experiments done at the PATBs in the hot humid climate. The results indicated that the urban spaces or specifically the plaza adjacent to tall buildings are acceptable given proper geometry and orientation considerations.